2020
DOI: 10.1111/cpr.12779
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondria‐targeted anti‐oxidant MitoQ protects against intervertebral disc degeneration by ameliorating mitochondrial dysfunction and redox imbalance

Abstract: Objective Mitochondrial dysfunction, oxidative stress and nucleus pulposus (NP) cell apoptosis are important contributors to the development and pathogenesis of intervertebral disc degeneration (IDD). Here, we comprehensively evaluated the effects of mitochondrial dynamics, mitophagic flux and Nrf2 signalling on the mitochondrial quality control, ROS production and NP cell survival in in vitro and ex vivo compression models of IDD and explored the effects of the mitochondria‐targeted anti‐oxidant MitoQ and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 73 publications
3
106
1
Order By: Relevance
“…In the result of MitoQ, only the fusion protein Mfn1 and the fission protein Fis1 showed similar trends to TE, but the expression of the other proteins (Mfn2, Opa1, and Drp1) did not differ from that in the D-CON group. Previous studies using cell culture systems demonstrated that MitoQ improved oxidative stress-disrupted mitochondrial dynamics balance [ 38 ], as well as mitochondrial fission in a pharmacological model of Parkinson’s disease, inducing mitochondrial fragmentation [ 39 ], which is inconsistent with our findings from in vivo experiment due to methodological differences between in vitro and in vivo experiment. Therefore, further studies using our animal model are warranted on the use of MitoQ and mitochondrial dynamics, including considerations of dose and treatment duration.…”
Section: Discussioncontrasting
confidence: 99%
“…In the result of MitoQ, only the fusion protein Mfn1 and the fission protein Fis1 showed similar trends to TE, but the expression of the other proteins (Mfn2, Opa1, and Drp1) did not differ from that in the D-CON group. Previous studies using cell culture systems demonstrated that MitoQ improved oxidative stress-disrupted mitochondrial dynamics balance [ 38 ], as well as mitochondrial fission in a pharmacological model of Parkinson’s disease, inducing mitochondrial fragmentation [ 39 ], which is inconsistent with our findings from in vivo experiment due to methodological differences between in vitro and in vivo experiment. Therefore, further studies using our animal model are warranted on the use of MitoQ and mitochondrial dynamics, including considerations of dose and treatment duration.…”
Section: Discussioncontrasting
confidence: 99%
“…Idebenone as a CoQ derivative could complement respiration in fibroblasts, while mitochondria-targeted CoQ derivative (MitoQ or ubiquinol) demonstrated to be 800-fold more potent than idebenone to prevent cell death [ 121 ]. Studying on compression-induced NP cells, MitoQ restored mitochondrial function and prevented the loss of mitochondrial ∆Ψ m and mitochondria-mediated apoptosis [ 122 ]. MitoQ balanced mitochondrial dynamics via upregulation of mitochondrial fusion (Mfn) molecules Mfn1and Mfn2 as well as downregulation of fission molecule Drp1 to prevent cell death.…”
Section: Small Molecules Targeting Mitochondrial Dysfunction In Ivd Degenerationmentioning
confidence: 99%
“…It also activated Nrf2 and its downstream molecules SOD 2 and NQO-1. Ex vivo study on rat tail disc has convincingly demonstrated the in vitro outcomes that MitoQ could re-organize AF collagen fibers, restored the size of NP tissue, and alleviated disc degeneration [ 122 ]. Overall, MitoQ would be a potent mitochondrial specific anti-oxidant that preserves mitochondrial homeostasis in NP cells.…”
Section: Small Molecules Targeting Mitochondrial Dysfunction In Ivd Degenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model of IDD, degenerative changes in IVDs in Nrf2-knockout mice were more severe than those in wild-type mice [ 3 ]. We previously reported that the activation of the Nrf2 cascade is an effective strategy to protect human disc cells from oxidative damage and prevent IDD progression [ 14 , 15 ]. Therefore, Nrf2 signal plays an important role in IDD characterized by oxidative stress.…”
Section: Introductionmentioning
confidence: 99%